2021
DOI: 10.3390/ijerph18136865
|View full text |Cite
|
Sign up to set email alerts
|

Profiles of Emotion Regulation and Post-Traumatic Stress Severity among Female Victims of Intimate Partner Violence

Abstract: Emotional dysregulation is a construct that has drawn substantial attention as a transdiagnostic contributing factor to the loss of health. Intimate partner violence (IPV) is a term used to describe physical, psychological, or sexual assault of a spouse or sexual partner. The aim of the study was to determine the variability of emotional dysregulation among women with different types of IPV revictimization and post-traumatic stress. The cross-sectional survey included 120 women attended by the Integrated Monit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 69 publications
1
16
1
Order By: Relevance
“…Secondly, this study identifies a new psychological mechanism underlying an IPV victim's WOHS. Although previous studies have shown that IPV causes PTSD [27], we further found that IPV can also induce ED symptoms in victims. When victims feel ED, they will have WOHS.…”
Section: Theoretical Contributionscontrasting
confidence: 94%
See 3 more Smart Citations
“…Secondly, this study identifies a new psychological mechanism underlying an IPV victim's WOHS. Although previous studies have shown that IPV causes PTSD [27], we further found that IPV can also induce ED symptoms in victims. When victims feel ED, they will have WOHS.…”
Section: Theoretical Contributionscontrasting
confidence: 94%
“…The index of moderated mediation and its 95% CI, as estimated by PROCESS, were used to determine and quantify the statistical significance of the moderated mediation effect [ 49 ]. The PROCESS macro has been widely used in the psychology field [ 27 ].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The term "emotional dysregulation" defines several conditions for which the patient appears to be unable to be aware of the emotions, to control impulsive behaviors, and to behave in line with the emotional status [44,45]. EDys seems to have a central role in many psychiatric diseases and internalized problems [12,[46][47][48]. The link between EDys and hypersexuality is dual.…”
Section: Evidencementioning
confidence: 99%